Macroeconomics: understanding the global economy - Miles, Breedon; Miles, Scott (Italy Wiley, 2012)
Revised and updated edition of a very successful macroeconomics textbook. Miles and Scott deal with sophisticated issues using advanced economic theory, but in a manner that is accessible to anyone taking a single course in macroeconomics. They begin with real-world economic issues, and describe why these matter, before embarking on economic theory, ensuring that readers emerge with a good practical understanding of the global economy and how economists think about it. This new edition has been completely revised and updated with current data, and features new material on key topics including globalization, aid and debt relief, and transition economies.
Age Group: Adult
Keywords: Economics; (ASB-3301) Macroeconomics